Budget impact analysis of boceprevir and telaprevir for the treatment of hepatitis C genotype 1 infection - El Khoury AC; Druyts E; Thorlund K; Mills EJ (Dove Medical Press, 2012)
Kristian Thorlund,1 Eric Druyts,2 Antoine C El Khoury,3 Edward J Mills21Department of Clinical Epidemiology and Biostatistics, McMaster University, Hamilton, 2Faculty of Health Sciences, University of Ottawa, Ottawa, Ontario, Canada; 3Merck Sharp and Dohme, Whitehouse Station, NJ, USABackground: Boceprevir and telaprevir have recently showed dramatically better treatment outcomes than conventional PEGylated interferon plus ribavirin for the treatment of hepatitis C virus genotype 1, but the average cost per patient is unknown.Methods: In the UK context, we performed a budget impact analysis to estimate the average per patient cost of adding boceprevir or telaprevir to PEGylated interferon plus ribavirin therapy. We considered both standard-duration therapy and response-guided therapy regimens of boceprevir and telaprevir for treatment-naïve and treatment-experienced patients. Our model utilized monthly discontinuation rates. We built a Bayesian Markov model to account for uncertainty associated with the clinical input and cost data.Results: The total average cost of response-guided therapy with boceprevir is £22,850 and £25,060 for treatment-naïve and treatment-experienced patients, respectively. By comparison, the total average cost of response-guided therapy with telaprevir was £29,930 and £31,880 for treatment-naïve and treatment-experienced patients, respectively, whereas the total average cost of standard-duration boceprevir is £34,680 and £34,350 and for telaprevir was £32,530 and £31,680 for treatment-naïve and treatment experienced patients, respectively.Conclusion: Our results demonstrate that response-guided therapy with boceprevir is notably less costly than response-guided therapy with telaprevir. Our results also suggest that the standard treatment duration of boceprevir is slightly more costly than the standard treatment duration of telaprevir.Keywords: hepatitis C, budget impact analysis, boceprevir, telaprevir